Variasi Bahasa Sosiolek Dalam Series Album “Kalih Welasku” Di Channel Youtube Denny Caknan - Tyas Nur Wigati; Anggita Ketlin Bella Pratiwi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Sociolectic language variations are one part of sociolinguistics. This research is entitled Sociolectic Language Variations in the Album Series "Kalih Welasku" on Denny Caknan's Youtube Channel. This panel discusses: the form of sociolect language variations in the "Kalih Welaksu" album series on Denny Caknan's YouTube channel and the causes of sociolect language variations in the "Kalih Welaksu" album series on Denny Caknan's YouTube channel. The aim of this research is to determine the form of sociolectic language variations in the "Kalih Welaksu" album series on Denny Caknan's YouTube channel and the causes of sociolectic language variations in the "Kalih Welaksu" album series on Denny Caknan's YouTube channel. The procedure for collecting data uses the listening and note-taking method. This data was analyzed using qualitative descriptive methods. This research uses a sociolinguistic approach. In this research, researchers found data on acolect types which contained the use of Javanese krama, English and Arabic, basilek type data, slang type dhata, vulgar type data, colloquial type data, jargon type data, ken type data.